Six steps to produce stock assessments for the Marine Strategy Framework Directive compliant with Descriptor 3. (26th February 2021) - Probst, Wolfgang Nikolaus; Kempf, Alexander; Taylor, Marc; Martinez, Inigo; Miller, David
Abstract: In the European Union (EU), the ecosystem approach to fisheries is implemented through several directives and polices, which are overarched by the Marine Strategy Framework Directive (MSFD). The MSFD requires the assessment of the environmental status of exploited fish and shellfish stocks, among others, to advise the EU Common Fisheries Policy (CFP) on sustainable catch options. The stock assessments for the CFP and the MSFD are supposed to be congruent, yet they differ in several substantial subjects. While the annual CFP assessment is based on two indicators, fishing mortality ( F ) and spawning stock biomass (SSB), in its Descriptor 3 (D3) the MSFD requires the assessment of three criteria ( F, SSB, and age or size structure) within a six year period. Assessing exploited fish and shellfish stocks under the MSFD by using existing CFP assessments has therefore been a half-completed task, which had to be fulfilled by the member states of the EU. This paper suggests six easy steps, referred to as "quick wins" (QW), which are based on existing information from CFP stock assessments. The implementation of these six QW would allow for assessments of exploited fish and shellfish stocks that are compliant to D3. These QW are to (i) assess length/age structure within a stock, (ii) analyse and assess selectivity by fisheries, (iii) use all available information to assess a stock, (iv) use response indicators to assess environmental targets, (v) provide integrated stock-specific advice, and (vi) provide assessments with a mid-term perspective over a-period of six years. International Council for the Exploration of the Sea (ICES) combines the infrastructure and expertise to produce stock-specific assessment products tailored to the requirements of MSFD D3. Thereby, ICES could provide a valuable service to EU member states in the north-east Atlantic region by providing scientifically validated, quality-assured, and MSFD-compliant single-stock assessment products. This would be a big advancement towards implementing the ecosystem approach to fisheries management within Europe.